The Role of Hip-Hop in Community Building and its Influence on Cluj-Napoca’s Young Urbanites “Concrete Rockers”. A Case Study - Bettina Ene; Iuliu Rațiu (Linguaculture)
This article examines the cultural influence of hip-hop on urban youth in Cluj-Napoca, Transylvania (Romania), through a case study of the “Concrete Rockers” Association. This dynamic group is deeply involved in hip-hop activities, with a particular emphasis on breakdancing, its core focus, as well as organizing hip-hop events such as “One May Jam”—the group’s flagship event. Here, members and special guests participate in various hip-hop activities like DJing and graffiti art. By exploring the motivations and experiences that drive these individuals to engage with hip-hop, we aim to gain insight into their roles as both consumers and practitioners of this culture. The article further investigates how group affiliation and identity are formed within this vibrant and close-knit community, while also exploring the Concrete Rockers’ aspirations to become prominent representatives of hip-hop in Transylvania. Our findings, based on primary data, offer a deeper understanding of hip-hop’s role in shaping the identities and lives of young adults in Cluj-Napoca, highlighting the local adaptations and transnational connections of this global movement and underscoring the positive impact hip-hop has on these individuals.